Heterogeneity of functional outcomes in patients with bipolar disorder: a cluster‐analytic approach. (5th March 2018) - Solé, B.; Bonnin, C. M.; Jiménez, E.; Torrent, C.; Torres, I.; Varo, C.; Valls, E.; Montejo, L.; Gómez‐Ocaña, C.; Tomioka, Y.; Vieta, E.; Martinez‐Aran, A.; et al.
Abstract : Objective: The aim was to examine the heterogeneity of psychosocial outcomes in euthymic bipolar disorder (BD) patients and analyse the potential influence of distinct variables on functioning. Method: Using a hierarchical cluster exploratory analysis, 143 euthymic patients with diagnosis of BD were grouped according to their functional performance based on domains scores of the Functioning Assessment Short Test (FAST). The resulting groups were compared on sociodemographic, clinical and neurocognitive variables to find factors associated with each functional cluster. Results: Patients were grouped in three functional profiles: patients with good functioning in all the FAST areas, patients with an intermediate profile showing great difficulties in the occupational domain and milder difficulties in most of the rest domains, and a third group with serious difficulties in almost all functional areas. Both functionally impaired groups were characterized by higher subthreshold symptoms (depressive and manic) and higher unemployment rates. The most functionally impaired group also showed lower scores on some measures of processing speed. Conclusion: Two of three functional profiles showed some kind of impairment which was associated with subsyndromal symptoms and cognitive performance. These patterns should be taken into consideration to develop more individualized interventions to restore, or improve, psychosocial outcomes.